Magnetic field–enhanced alkaline water electrolysis from laboratory to industry - Hao Li; Jiakun Fang; Danji Huang; Zhiyao Zhong; Qunlei Wen; Youwen Liu; Kewei Hu; Zhenhong Yang; Ang Lu; Xiaomeng Ai; Tianyou Zhai; Jinyu Wen; et al. (Proceedings of the National Academy of Sciences, 2026)
The fundamental limitation of water oxidation in alkaline water electrolysis (AWE) lies in the progressive depletion of dynamic active sites and rapid dissipation of local active ion concentration, a critical thermodynamic constraint that conventional electrochemical strategies struggle to overcome. Here, we propose a magnetic field–enhanced AWE (ME-AWE) strategy that enables in-situ directional enrichment of local active iron ions near the anode, thus breaking the concentration limit and boosting the coverage of dynamic iron active sites without elevating bulk impurity levels. Laboratory-scale three-electrode experiments confirm improved oxygen evolution reaction (OER) kinetics by the magnetically induced optimization of iron incorporation dynamics and the increase in the coverage of dynamic iron active sites. A multiphysics model coupling magnetic field, fluid flow, mass transport, and electrochemical reaction is developed to spatially interpret the mechanism, revealing that the magnetic modulation enables OER kinetics at 0.3 ppm iron equivalent to those at tenfold higher concentration without a magnetic field. Guided by mechanistic insights, an industry-scale ME-AWE device is designed and implemented, achieving a 24.9% increase in hydrogen output at 1.8 V. Techno-economic analysis demonstrates that the ME-AWE strategy enables a 10.6% reduction in total AWE capital cost for large-scale hydrogen production plants using off-grid wind power. Built with existing industrial infrastructure, this ME-AWE strategy offers a scalable and low-cost solution for improving AWE efficiency and advancing impurity-assisted catalysis in green hydrogen production.